2022
DOI: 10.1186/s12974-022-02435-9
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota is causally associated with poststroke cognitive impairment through lipopolysaccharide and butyrate

Abstract: Background Poststroke cognitive impairment (PSCI) is prevalent in stroke patients. The etiology of PSCI remains largely unknown. We previously found that stroke induces gut microbiota dysbiosis which affects brain injury. Hereby, we aimed to investigate whether the gut microbiota contributes to the pathogenesis of PSCI. Methods 83 stroke patients were recruited and their cognitive function were measured by Montreal Cognitive Assessment (MoCA) score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…SCFAs can enter the circulatory system and may signal the brain [ 28 ]. SCFAs also regulate the maturation and function of microglia and prevent neuroinflammatory processes [ 29 , 30 ]. Although we previously found that Mel alleviates cognitive impairment in sleep-deprived mice, its mechanism of action remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…SCFAs can enter the circulatory system and may signal the brain [ 28 ]. SCFAs also regulate the maturation and function of microglia and prevent neuroinflammatory processes [ 29 , 30 ]. Although we previously found that Mel alleviates cognitive impairment in sleep-deprived mice, its mechanism of action remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our macrogenomic results give further clues - the lipopolysaccharide core region biosynthesis is significantly increased. The relationship between gut microbiome and stroke inflammation continues to be demonstrated, with gut dysbiosis in stroke patients and secreted pro-inflammatory molecules activating the systemic inflammatory response, leading to increased neuroinflammation ( Wang et al., 2022 ; Wang et al., 2022 ). Zheng Q et al.…”
Section: Discussionmentioning
confidence: 99%
“…found that Klebsiella, Escherichia-Shigella, and Bacteroides were positively correlated with systemic inflammatory markers in stroke patients ( Zheng et al., 2022 ). Mice received fecal bacteria transplantation from stroke patients or injection of Lipopolysaccharide exacerbated the neuroinflammatory response ( Wang et al., 2022 ). Our findings further explain the above phenomenon that active synthesis of pro-inflammatory molecules by gut microbiome in ICH patients promotes a systemic inflammatory response, ultimately lead to increased neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Normalization of brain lesion-induced dysbiosis via FMT improved stroke outcome in experimental stroke models (Lee, d'Aigle, et al, 2020;Lee, Venna, et al, 2020;Spychala et al, 2018;Yamashiro et al, 2017). Although beneficial effects have been observed in animal stroke models, FMT trials conducted in patients who suffered stroke so far do not provide evidence of a beneficial effect (H. Wang et al, 2022;H. M. Xu et al, 2021).…”
Section: Faecal Microbiota Transplantation (Fmt)mentioning
confidence: 99%